Barriers to accessing and continuing mental health treatment among individuals with dissociative symptoms. Issue 1 (31st December 2022) - Nester, M. Shae; Hawkins, Sarah L.; Brand, Bethany L.
ABSTRACT: Background: Dissociative disorders (DDs) are characterized by interruptions of identity, thought, memory, emotion, perception, and consciousness. Patients with DDs are at high risk for engaging in dangerous behaviours, such as self-harm and suicidal acts; yet, only between 28% and 48% of individuals with DDs receive mental health treatment. Patients that do pursue treatment are often misdiagnosed, repeatedly hospitalized, and experience disbelief from providers about their trauma history and dissociative symptoms. Lack of dissociation-specific treatment can result in poor quality of life, severe symptoms requiring utilization of hospitalization and intensive outpatient treatment, and high rates of disability. Objective: Given the extensive and debilitating symptoms experienced by individuals with DDs and the infrequent utilization of treatment, the current study explored barriers to accessing and continuing mental health treatment for individuals with dissociative symptoms and DDs. Method: A total of 276 participants with self-reported dissociative symptoms were recruited via online social media platforms. Participants completed a survey which featured 35 possible barriers to accessing treatment and 45 possible reasons for discontinuing treatment, along with open text boxes for adding barriers/reasons that were not listed. Results: Results showed 97% of participants experienced one or more barriers to accessing treatment ( M = 9 barriers) and 92% stopped treatment with a provider due to at least one of the reasons captured in the survey (e.g. limited insurance coverage, poor therapeutic alliance, disbelief from providers, etc.; M = 7 barriers). Conclusions: The most frequently endorsed barriers were structural barriers, such as those related to finances, insurance, and lack of provider availability. It is imperative more service providers are trained to treat dissociation and that insurers and health care systems recognize the need for specialized, dissociation-focused treatment. HIGHLIGHTS: Most dissociative individuals reported barriers to accessing and continuing mental health treatment. It is imperative more clinicians are trained to treat dissociation and that insurers and health care systems recognize the need for specialized, dissociation treatment.